Organizational Resilience and Its Influence on Nurse Turnover Intention, Workplace Accidents, and Psychological Safety in Healthcare Systems - Agustiningsih, Ida; Agustin, Ratna; Mundakir, Mundakir (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2025)
Background: Organizational resilience is increasingly recognized as a key capability for healthcare systems to manage workforce challenges and safety risks. However, its simultaneous influence on turnover intention, workplace accidents, and psychological safety remains underexplored. Objective: This study aimed to examine the influence of organizational resilience on turnover intention, workplace accidents, and psychological safety among healthcare workers in hospital settings. Methods: A cross-sectional analytical study was conducted among 258 healthcare workers, including nurses, doctors, medical support staff, and administrative personnel, using cluster sampling. Organizational resilience was measured using a modified Organizational Resilience Questionnaire focusing on planning and adaptive capacity domains. Turnover intention, workplace accidents, and psychological safety were assessed using validated instruments. Data were analyzed using descriptive statistics and Pearson correlation analysis. Results: The mean score of organizational resilience was 3.78 ± 0.54. Organizational resilience showed a significant negative correlation with turnover intention (r = -0.512, p < 0.001) and workplace accidents (r = -0.389, p < 0.001), indicating that higher resilience was associated with lower intention to leave and fewer occupational incidents. In contrast, organizational resilience demonstrated a positive correlation with psychological safety (r = 0.559, p < 0.001), reflecting a stronger perception of a safe work environment. Among the outcomes, psychological safety showed the strongest association, followed by turnover intention and workplace accidents. Conclusion: Organizational resilience plays a critical role in reducing turnover intention and workplace accidents while enhancing psychological safety, highlighting its importance in strengthening workforce sustainability and healthcare quality.